Awareness about expressed breast milk feeding among working mothers visiting a tertiary level hospital, Kathmandu - Pandey, Shrijana (Journal of Kathmandu Medical College, 2019)
Background: Expressed breast milk can be a healthy feeding option as compared to formula for working mothers. A large number of mothers are working these days and despite their desire to breastfeed, mothers have to get back to their work because of various constraints.Objectives: The research objective was to assess the status of knowledge and attitude regarding expressed breastfeeding and to identify the barriers to expressed breastfeeding among working mothers visiting Kathmandu Medical College Teaching Hospital.Methodology: A cross-sectional study was conducted at Pediatric Outpatient Department of Kathmandu Medical College Teaching Hospital from June 2018 till December 2018. One hundred and eighty working mothers were chosen purposively and interviewed. Research instrument was a structured questionnaire containing questions about technique of pumping and storing breast milk, benefits of breastfeeding, attitude regarding expressed breastfeeding and reasons for not expressing breast milk. Mean standard deviation and Chi-square tests were used for statistical analysis.Results: Out of 180 mothers, half of the mothers had adequate knowledge regarding expressed breastfeeding while slightly more than half of them (52.2%) had negative attitude about it. Only 11.7% of the mothers shared that they had expressed breast milk ever. The most important reason for not expressing breast milk was stated to be inadequate breast milk production (30.7%) and lack of time (26.4%).Conclusion: The study concludes that about half of the working mothers have adequate knowledge and positive attitude regarding expressed breastfeeding. Moreover, very few mothers ever expressed breast milk and the main reason for not doing so was inadequate milk production.